Nina wonders, Nina asks - Lee, Marcy Dans (UNICEF, 2015)
"Marcy wrote and Marcy drew the storybooks, she's done a few for Marcy wanted kids to know the happy things with which to grow. Marcy loves her work so true and hopes that you will like it too. Marcy thinks and Marcy prays that she can write and draw all day."--Page 4 of cover.